A Phenomic Perspective on Factors Influencing Breast Cancer Treatment: Integrating Aging and Lifestyle in Blood and Tissue Biomarker Profiling - Arana Echarri, Ainhoa; Beresford, Mark; Campbell, John P.; Jones, Robert H.; Butler, Rachel; Gollob, Kenneth J.; Brum, Patricia C.; Thompson, Dylan; Turner, James E. (Frontiers in Immunology, 2021)
Breast cancer is the most common malignancy among women worldwide. Over the last four decades, diagnostic and therapeutic procedures have improved substantially, giving patients with localised disease a better chance of cure, and those with more advanced cancer, longer periods of disease control and survival. However, understanding and managing heterogeneity in the clinical response exhibited by patients remains a challenge. For some treatments, biomarkers are available to inform therapeutic options, assess pathological response and predict clinical outcomes. Nevertheless, some measurements are not employed universally and lack sensitivity and specificity, which might be influenced by tissue-specific alterations associated with ageing and lifestyle. The first part of this article summarises available and emerging biomarkers for clinical use, such as measurements that can be made in tumour biopsies or blood samples, including so-called liquid biopsies. The second part of this article outlines underappreciated factors that could influence the interpretation of these clinical measurements and affect treatment outcomes. For example, it has been shown that both adiposity and physical activity can modify the characteristics of tumours and surrounding tissues. In addition, evidence shows that inflammageing and immunosenescence interact with treatment and clinical outcomes and could be considered prognostic and predictive factors in isolation. In summary, changes to blood and tissues that reflect ageing and patient characteristics, including lifestyle, are not commonly considered clinically or in research, either for practical reasons or because the supporting evidence base is developing. Thus, an aim of this article is to encourage an integrative phenomic approach in oncology research and clinical management.